Two Cancer Patients Receiving Dupilumab for Treatment of Atopic Dermatitis - Emilie Fowler; Jordan Rosen; Hadar Lev-Tov; Gil Yosipovitch (Medical Journals Sweden, 2019)
Abstract is missing (short communication)